Which Way Goes Romanian Capitalism? – Making a Case for Reforms, Inclusive Institutions and a Better Functioning European Union - Daniel Dăianu; Bogdan Murgescu (Romanian Journal of European Affairs)
This paper examines the Romanian economy and its version of capitalism from a long-term perspective and in a broad context. It focuses on economic prospects in the face of a legacy of backwardness and the endurance of domestic weaknesses, in the context of the Great Recession and the eurozone crisis. Romania has a pressing need to mobilise its internal resources and absorb EU funds on a much greater scale so that it can enhance economic growth and mitigate external shocks. To this end, Romania needs to undertake thorough reforms in the public sector, combat rent-seeking and waste, foster domestic savings. The functioning of institutions and of taxation should convey a sense of fairness to citizens. Romania needs to rethink its growth model. Romania must improve its education system by increasing the level of resources assigned to education and creating coherent policies to strengthen institutional capacities and to improve quality standards. The Romanian economy would benefit significantly from EU policies that are more responsive to the economic and social fractures revealed by the current crisis. Not least, financial markets have to be tamed in Europe and elsewhere if they are to serve economies.